(untitled) (Fiep Bulletin - online, 2014)
The modern education in kindergartens interested in studying childhood and care of is one of the most important criteria that measured by the inclinations and the natural capacities of the child, which aims to invest energies child, and working on his preparation for life. The kindergarten of the most important stages needed by the child in his childhood, where he became (kindergarten) educational institutions play a significant role in the lives of mother and child is one of the most important stages of her-his growth. The Higher Committee for Children of the UN reported that the child in need of protection before and after his birth, as it is the child’s right to enjoy health care, spiritual, social, and obtained the right to food, sports and live among parents. And the use of animated stories in the style aspects of learning helps the child to gain a lot of social skills, and is also working on the development of the activity Sports Movement to her- him. This paper aims to achieve some of the goals of which show the importance of attention to social and sports component in children, and through the use of stories (cartoons and movies) moving in kindergarten (4-6 years).